2016
DOI: 10.1002/cbic.201600322
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a Conserved Lys/Arg Residue for Ligand/PDZ Domain Interactions as Examined by Protein Semisynthesis

Abstract: PDZ domains are ubiquitous small protein domains that are mediators of numerous protein-protein interactions, and play a pivotal role in protein trafficking, synaptic transmission, and the assembly of signaling-transduction complexes. In recent years, PDZ domains have emerged as novel and exciting drug targets for diseases (in the brain in particular), so understanding the molecular details of PDZ domain interactions is of fundamental importance. PDZ domains bind to a protein partner at either a C-terminal pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
(131 reference statements)
1
6
0
Order By: Relevance
“…The FP saturation assays showed that the cyclic nNOS peptide bound to both PSD-95-PDZ1 (K d = 3.4 ± 0.3 μM) and PSD-95-PDZ2 (K d = 1.0 ± 0.1 μM) (Figures 1B and S1) while binding with much lower affinity to PSD-95-PDZ3 (K d = 52.0 ± 10.5 μM). These results align with previous binding studies using a cyclic nNOS β-hairpin mimetic peptide 45,46 and the nNOS-PDZ-β-hairpin protein. 53 Additionally, we verified that cyclization was a requirement for the β-hairpin mimetic to bind to PSD-95-PDZ2 by employing isothermal titration calorimetry (ITC).…”
Section: Synthesis Of An Nnos β-Hairpin Cyclic Peptide Usingsupporting
confidence: 91%
See 3 more Smart Citations
“…The FP saturation assays showed that the cyclic nNOS peptide bound to both PSD-95-PDZ1 (K d = 3.4 ± 0.3 μM) and PSD-95-PDZ2 (K d = 1.0 ± 0.1 μM) (Figures 1B and S1) while binding with much lower affinity to PSD-95-PDZ3 (K d = 52.0 ± 10.5 μM). These results align with previous binding studies using a cyclic nNOS β-hairpin mimetic peptide 45,46 and the nNOS-PDZ-β-hairpin protein. 53 Additionally, we verified that cyclization was a requirement for the β-hairpin mimetic to bind to PSD-95-PDZ2 by employing isothermal titration calorimetry (ITC).…”
Section: Synthesis Of An Nnos β-Hairpin Cyclic Peptide Usingsupporting
confidence: 91%
“…This residue was reported to be responsible for binding to the carboxylate terminus of canonical peptides, yet nNOS lacks this carboxylic terminus. 46 PSD-95-PDZ2 containing the F172A mutation in the β-strand B (βB) did not fold according to circular dichroism (CD). Instead, we introduced an F172I mutation, which is the corresponding residue of the syntrophin-1-PDZ domain (Figure S19).…”
Section: High-throughput Arrays Of Cyclic Backbone Hairpin Peptides�n...mentioning
confidence: 99%
See 2 more Smart Citations
“…We know that the β-finger ligand from the PDZ domain of nNOS forms an extended antiparallel β-sheet which interacts with the binding groove on the α-syntrophin PDZ domain to form a heterodimer (Hillier et al 1999). PDZ protein interaction domains are among the most common protein modules, and in recent years have emerged as novel drug targets for disease (Pedersen et al 2016), thus highlighting their potential in the development of tailored interfaces at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%